International financial management - Rodriguez, Rita M.; Carter, E. Eugene (Englewood Cliffs, N.J. : Prentice-Hall, 1984)
The introductory chapter presents an outline for the students about this text and offers some historical information about foreign investment by the United States over the last several decades. The text is ideally designed for upper- level undergraduates or MBA/MS students who have completed introductory courses in finance and economics.
Includes bibliographical references and index.
hza 02/08/2018
Loans
Keywords: International finance; International business enterprises